2016
DOI: 10.1017/s0029665116002342
|View full text |Cite
|
Sign up to set email alerts
|

FoodFinder: developing a rapid low-cost crowdsourcing approach for obtaining data on meal size from meal photos

Abstract: Capturing meal images using mobile phone cameras is a promising alternative to traditional dietary assessment methods. Acquiring photos is reasonably simple but nutritional content analysis of images is a major challenge. Automated food identification and portion size assessment is computationally and participant intensive; relying on participant feedback for accuracy (1) . Dietitian analysis of photos is accurate but time-consuming and expensive (2) . Crowdsourcing could offer a rapid low-cost alternative by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…For each of these photos total meal weight was measured using an Mandometer® device (Mikrodidakt AB, Lund, Sweden) and food groups displayed were reviewed by an expert dietitian. In comparison to the measured weight, crowds underestimated meal weight by an average of 63 g (95% level of agreement -299 to 174 g), whereas the dietitian overestimated by 28 g (95% level of agreement -158 to 214 g) 15 . In further analyses, we found that compared with expert dietician review, crowds varying in size from 5 to 50 people identified food groups in the photos with high specificity (mean 98%) but modest sensitivity (68%) i.e.…”
Section: Pilot Data Collection Of Physical Activity and Dietmentioning
confidence: 77%
“…For each of these photos total meal weight was measured using an Mandometer® device (Mikrodidakt AB, Lund, Sweden) and food groups displayed were reviewed by an expert dietitian. In comparison to the measured weight, crowds underestimated meal weight by an average of 63 g (95% level of agreement -299 to 174 g), whereas the dietitian overestimated by 28 g (95% level of agreement -158 to 214 g) 15 . In further analyses, we found that compared with expert dietician review, crowds varying in size from 5 to 50 people identified food groups in the photos with high specificity (mean 98%) but modest sensitivity (68%) i.e.…”
Section: Pilot Data Collection Of Physical Activity and Dietmentioning
confidence: 77%
“…Depending on the needs of the particular scenario, and balancing speed, accuracy, and cost, data from the central profile may be sent for further analysis. For example, images of meals may be sent to a crowd-based application (44), or a dietician to refine food item identification and portion sizes (72).…”
Section: Integrating Methodsmentioning
confidence: 99%
“…To be feasible for use in large-scale longitudinal studies or public health interventions, crowdsourcing of food data from photographs needs to be fast and low cost. We developed and piloted a novel system, FoodFinder (44), and found that small (n = 5) untrained crowds could rapidly classify foods and estimate meal weight in 3 min for £3.35 per photo. Crowds underestimated measured meal weight by 15% compared with 9% overestimation by an expert.…”
Section: What We Eatmentioning
confidence: 99%
“…Depending on the needs of the particular scenario, and balancing speed, accuracy, and cost, data from the central profile may be sent for further analysis. For example, images of meals may be sent to a crowd-based application 42 , or a dietician to refine food item identification and portion sizes 68 .…”
Section: Integrating Methodsmentioning
confidence: 99%
“…To be feasible for use in large-scale longitudinal studies or public health interventions, crowdsourcing of food data from photographs needs to be fast and low cost. We developed and piloted a novel system, FoodFinder 42 , and found that small (n=5) untrained crowds could rapidly classify foods and estimate meal weight in 3 min for £3.35 per photo. Crowds underestimated measured meal weight by 15% compared with 9% overestimation by an expert.…”
Section: What We Eatmentioning
confidence: 99%